Three Pillars of Novel Nonthermal Food Technologies: Food Safety, Quality, and Environment - Anet Režek Jambrak; Tomislava Vukušić; Francesco Donsi; Larysa Paniwnyk; Ilija Djekic (Journal of Food Quality)
This review gives an overview of the impact of novel nonthermal food technologies on food safety, on quality, and on the environment. It confirms that research in this field is mainly focused on analyzing microbial and/or chemical aspects of food safety. However, recent research shows that in spite of various food safety benefits, some negative (quality oriented) features occur. Finally, this paper shows the necessity of analyzing the environmental dimension of using these technologies.